Development of mechanisms to reduce market distortions in Ethiopian small ruminant value chains - CGIAR Research Program on Livestock (2018)
Policy and development options have been identified to minimise policy-induced price distortions in small ruminants markets. The options were developed based on empirical findings of a study that covered the small ruminant value chains in the whole of Ethiopia (article in press: Journal of Agribusiness in Developing and Emerging Economies).